Cultura da convergência aplicada ao ensino da tabela periódica - Silva, Poliana Pereira da (2020)
The present investigation deals with the elaboration, application and analysis of a teaching strategy aimed at Science teachers who wish to work with Information and Communication Technologies (ICT), in the teaching of the Periodic Table, in a playful and assertive manner. From the perspective of the Convergence Culture (JENKINS, 2009) we used smartphones and social networks as allies throughout the process. From the central question "How can the Convergence Culture contribute to the inclusion of ICT in the teaching of the Periodic Table?" the present research emerged. We seek, as a general objective, to understand how the Convergence Culture, through a didactic sequence (SD), can contribute to the insertion of ICT in the teaching of the Periodic Table. In order to develop the theme better, in addition to the mentioned author, we rely on: Marchand (1987) and Silva (2003; 2014), with statements about communication; Lévy (1999), with contributions on interactivity; Prensky (2001), with concepts about Natives and Digital Immigrants; Vasconcelos (2016; 2017), highlighting the social interactions that emerged from virtual communities and interactivity in the educational context; Braga (2013), with reflections on the changes in the process of teaching and learning; Castells (1999), with his classic approach to the ICT revolution; César, Reis and Aliane (2015), with reflections on the teaching of the Periodic Table; Delizoicov, Angotti and Pernambuco (2009), establishing the pedagogical moments for an SD; Ausubel (1963, 2003), about meaningful learning; among others. With a qualitative approach (MINAYO, 2001), and an investigation into practice (PONTE, 2002), the research was applied to 26 students from the 9th grade of elementary school in a state public school located in the municipality of Aracaju/SE. The activities developed - interactive lecture, image contest and stop motion - throughout the investigation led to the creation of a Giant Periodic Table. Data were collected through a probing test, written records by students, observations made by the teacher/researcher and comments on social networks. For data analysis we used an adaptation of content analysis (BARDIN, 1977) creating four categories of analysis. In view of the results obtained, we verified that the Convergence Culture contributes to the inclusion of ICT in the teaching of the Periodic Table: 1) using technological resources accessible to most students; 2) encouraging the teacher to assume the role of advisor, facilitator, supervisor and mediator of the teaching-learning process; 3) promoting situations where the processing of meaningful learning takes place through reception and discovery, simultaneously and, last but not least, 4) potentiating several other aspects, such as, for example, student engagement and autonomy, the student-teacher relationship, among others, which as well as these can even be objects of future research involving the Convergence Culture and the Chemistry Teaching.